Types and Function of Euphemism in Minangkabaunese Used by Adults in Ulakan Tapakis - Sofyan, Camelia; Jufrizal, Jufrizal (Universitas Negeri Padang, 2023)
This study focused on the euphemisms in Minangkabaunese used by adults in Ulakan Tapakis which analysts the types and functions. This research used the descriptive qualitative method, which describes the data that the researcher collected in the form of sentences with the exact meaning possible. The data were euphemism utterances in the form of word, phrase, and sentence uttered by Minangkabaunese adults in Ulakan Tapakis. The researcher found that from all seven types of euphemism, the Adults of Ulakan Tapakis society often euphemism with word or phrase dealing with harsh word or sensitive words, which directed at characters and circumstance euphemism, obituary/incident euphemism, bodily part, diseases of euphemism, activity, occupation, and also things and animals. The researcher also found from five functions of euphemism, the society often used euphemism with the word or phrase for polite function, hide something, also for refuse danger.